PERANCANGAN APLIKASI PENJUALAN DILENGKAPI PROMOSI DAN CASHBACK BERBASIS ANDROID - Vina Fariska; Muhammat Rasid Ridho (Computer Based Information System Journal, 2025)
In the context of Android-based sales applications, these two features can be integrated to provide added value and greater competitiveness in the digital era. The aim of this research is to design a strategy to increase online sales through designing a sales application equipped with Android-based promotions and cashback at CV Abang Putra Grosir. This research uses the Scrum method to develop the required applications including the stages of problem identification, data collection, program design using UML, system building, system testing, as well as results and conclusions. The research object used was the Abang Putra Jaya retail and wholesale store. The research results state that the new application-based system is much more efficient than the old system. Older systems, such as recording sales transactions in books or spreadsheets, are prone to human error, very time-consuming and often take a long time, especially searching for previously recorded data or reports. In terms of effectiveness, the new system is also better than the old system. Manual systems, which rely on physical record keeping or use spreadsheets, are prone to human error in data input, which can impact the quality of reports and decisions made. In contrast, the new system records transactions automatically and in an integrated manner, which reduces the risk of errors and increases data accuracy.